2011
DOI: 10.1124/dmd.111.042861
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Aldehyde Oxidase Enzyme Activity in Cryopreserved Human Hepatocytes

Abstract: ABSTRACT:Substrates of aldehyde oxidase (AO), for which human clinical pharmacokinetics are reported, were selected and evaluated in pooled mixed-gender cryopreserved human hepatocytes in an effort to quantitatively characterize AO activity. confirmed that the predominant oxidative metabolite was generated by AO, as expected isotope patterns in mass spectra were observed after analysis by high-resolution mass spectrometry. Second, clearance values were efficiently attenuated upon coincubation with hydralazine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(69 citation statements)
references
References 30 publications
3
66
0
Order By: Relevance
“…In addition to the potent inhibition of GDC-0834 metabolism by AO inhibitors, GDC-0834 also inhibits the metabolism of several known AO substrates carbazeran, DACA, O 6 -benzylguanine, phthalazine, zaleplon, and zoniporide (Beedham et al, 1990;Beedham et al, 1995;Kawashima et al, 1999;Schofield et al, 2000;Obach et al, 2004;Dalvie et al, 2012;Hutzler et al, 2012) (Fig. 4, A-F).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to the potent inhibition of GDC-0834 metabolism by AO inhibitors, GDC-0834 also inhibits the metabolism of several known AO substrates carbazeran, DACA, O 6 -benzylguanine, phthalazine, zaleplon, and zoniporide (Beedham et al, 1990;Beedham et al, 1995;Kawashima et al, 1999;Schofield et al, 2000;Obach et al, 2004;Dalvie et al, 2012;Hutzler et al, 2012) (Fig. 4, A-F).…”
Section: Discussionmentioning
confidence: 97%
“…In a recent report, our laboratory demonstrated that the predominant metabolite after incubation of BIBX1382 in cryopreserved human hepatocytes had a retention time and fragmentation pattern matching that of the authentic standard metabolite, BIBU1476 (4-[(3-chloro-4-fluorophenyl)amino]-6-[(1-methylpiperidin-4-yl)amino]pyrimido [5,4-day]pyrimidin-2(4aH)-one), with the position of oxidation occurring on the pyrimido-pyrimidine core ( Fig. 1) (Hutzler et al, 2012). The role of aldehyde oxidase in the production of BIBU1476 was confirmed by a decrease in the observed in vitro clearance in cryopreserved human hepatocytes when the AO-selective inhibitor hydralazine was coincubated (Hutzler et al, 2012), an in vitro phenotyping methodology also reported by Strelevitz et al (2012).…”
mentioning
confidence: 83%
“…Based on analysis of chemical structure, a recent review suggested that a large number of drugs on the market (;13%) or candidate drugs (almost 45% of drugs in development) could be AO substrates (Pryde et al, 2010). With the increasing role of AO in drug metabolism, ongoing research activities have focused exclusively on the human liver (Obach et al, 2004;Hutzler et al, 2012Hutzler et al, , 2014, even if gene expression (Nishimura and Naito, 2006) and immunohistochemistry (Moriwaki et al, 2001) studies suggested a considerable extrahepatic presence, especially in kidneys and lungs. Moreover, efforts to predict AO clearance in vivo based on in vitro assays in hepatic experimental models generally resulted in underestimation (Zientek et al, 2010;Hutzler et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing role of AO in drug metabolism, ongoing research activities have focused exclusively on the human liver (Obach et al, 2004;Hutzler et al, 2012Hutzler et al, , 2014, even if gene expression (Nishimura and Naito, 2006) and immunohistochemistry (Moriwaki et al, 2001) studies suggested a considerable extrahepatic presence, especially in kidneys and lungs. Moreover, efforts to predict AO clearance in vivo based on in vitro assays in hepatic experimental models generally resulted in underestimation (Zientek et al, 2010;Hutzler et al, 2012). The mRNA and protein expressions of AO were recently also detected in human skin van Eijl et al, 2012), but its activity to date remains unknown.…”
Section: Discussionmentioning
confidence: 99%